2017
DOI: 10.2106/jbjs.16.00223
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Reverse Total Shoulder Arthroplasty

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
149
3
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(176 citation statements)
references
References 26 publications
9
149
3
15
Order By: Relevance
“…Even if the author encouraged caution in using a reverse prosthesis in young patients because of degradation of functional results, an important factor in his study is also the cause of the shoulder dysfunction; failure of a previous implant and posttraumatic arthritis are associated with a greater decrease in functional outcomes, whereas CTA and primary osteoarthritis have the best long-term results, with preserved mobility and active anterior elevation. 2 Despite these considerations, today there is a tendency to extend the indications to younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the author encouraged caution in using a reverse prosthesis in young patients because of degradation of functional results, an important factor in his study is also the cause of the shoulder dysfunction; failure of a previous implant and posttraumatic arthritis are associated with a greater decrease in functional outcomes, whereas CTA and primary osteoarthritis have the best long-term results, with preserved mobility and active anterior elevation. 2 Despite these considerations, today there is a tendency to extend the indications to younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…outcomes 7,8,12,15,43,48 that seem to persist in long-term studies. 2,23,43 A reduction in active external and internal rotation and scapular notching were underlined as the limits of Grammont's classic design. 6,7,46 Several biomechanical studies showed that increasing the lateral offset is an effective solution in recovering rotational movement and avoiding scapular notching.…”
mentioning
confidence: 99%
“…Furthermore, the significant differences in measured peak elevation muscle moment arms between the anatomic and reverse shoulder varied from 7.7 mm (superior infraspinatus during abduction) to 21.5 mm (middle deltoid during flexion). The combined changes in moment arms of these and other shoulder muscles are likely to be the primary contributor to the marked differences in estimated muscle recruitment patterns and glenohumeral joint force following RSA, which have been shown to be clinically relevant …”
Section: Discussionmentioning
confidence: 99%
“…4 Long term results have been reported and continue to be evaluated. 5 From an economic standpoint, studies have shown RTSA to be more cost-effective than Total Shoulder Arthroplasty (TSA) and Hemi-arthroplasty (HA) with respect to cost of implant and low rate of complication from the surgery. [6][7][8] Anecdotally, we have noticed patients with a complaint of limited range of motion at the end of one year possibly due to the delay in the onset of shoulder motion.…”
Section: Introductionmentioning
confidence: 99%